Biomimetic Synthesis of Calcium Carbonate in the Sucrose Solution - YAO*, CHENG-LI; XU†, WANG-HUA; DING, AI-MIN; ZHU, JIN-MIAO (Asian Journal of Chemistry, 2009)
Many studies showed that saccharides or polysaccharides play an important role in the process of biomineralization. In this work, sucrose was used to induce the formation of calcium carbonate. The CaCO3 crystals were characterized by scanning electron microscope (SEM), Fourier transform infrared spectrograph (FT-IR) and powder X-ray diffractometry (XRD). The results showed vaterite formed easily in the sucrose solution.